2020
DOI: 10.21608/jssae.2020.160919
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zeolite Soil addition under Different Irrigation Intervals on Maize Yield (zea mays L.) and some Soil Properties

Abstract: The adequate supply of irrigation water is a crucial factor controlling the growth and productivity of crops.Under water poverty conditions in Egypt and most arid regions, sustaining the irrigation water in the root zone as long as possible becomes very necessary.Consequently, two field trials were performed aiming to evaluate the effect of zeolite soil addition of as main plots[ Z0:without zeolite(control)and Z1: with zeolite at rate of 10 Mg h -1 ]under three irrigation intervals as subplots [I1: irrigation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
2
8
0
Order By: Relevance
“…Ag nanoparticle is also important to encounter oxidative and osmotic stresses (Khan and Bano, 2016). These results are in harmony with those reported by El-Sherpiny et al (2020); Gomaa et al (2021 a, b); Tefera (2021) who indicated that using Si or AgNPs or its combination increased yield and yield components.…”
Section: Resultssupporting
confidence: 85%
“…Ag nanoparticle is also important to encounter oxidative and osmotic stresses (Khan and Bano, 2016). These results are in harmony with those reported by El-Sherpiny et al (2020); Gomaa et al (2021 a, b); Tefera (2021) who indicated that using Si or AgNPs or its combination increased yield and yield components.…”
Section: Resultssupporting
confidence: 85%
“…Also, it has an important role in preventing soil moisture losses (Khalifa et al, 2019). Generally, it can be said that zeolite possesses a vital role in reducing the added synthetic nitrogen fertilizers due to its ability to hold the mineral nitrogen forms as long as possible (El-Sherpiny et al, 2020), consequently slow-release of its and increasing efficiency of synthetic nitrogen fertilizers.…”
Section: Discussionmentioning
confidence: 99%
“…There are many recent studies that talked about the possibility of raising the efficiency of mineral fertilization of the nitrogen element by mixing it with zeolite conditioner (Bernardi et al, 2009;Azarpour et al, 2011;Khalifa et al, 2019;El-Sherpiny et al, 2020). Zeolite is among the most hydrated minerals on the surface of the earth and is found in a myriad of environments, including soils.…”
Section: Introductionmentioning
confidence: 99%
“…The surge in the poultry and livestock industry has further led to a substantial increase in maize consumption in animal feeds. Recognized as a lucrative grain crop, maize stands out as one of the most versatile globally (El-Sherpiny et al 2020).…”
Section: Introductionmentioning
confidence: 99%